Implementasi Festival Anak sebagai Sarana Pengembangan Prestasi dan Kreativitas Generasi Muda di Kelurahan Aek Kota Batu - Fadila, Maulia; Siregar, Diyan Mentari; Nasution, Iwan; Khairani, Yesa Dwi; Tanjung, Alhilalwi Anwar (Yayasan Kawanad, 2025)
The Children's Festival is one of the main programs of the Community Service (KKN) conducted by Universitas Islam Negeri Sumatera Utara (UINSU) in Aek Kota Batu Village. This activity aims to foster achievement, creativity, and Islamic values among the younger generation through non-formal activities that are both educational and recreational. The implementation method used a participatory approach by involving the community, schools, religious leaders, and local youth. The festival was held for two days: on August 23, 2025, featuring Qur'an Recitation (Tartil) and Juz 'Amma Memorization competitions, and on August 24, 2025, featuring Coloring, Fashion Show, Religious Speech, and Adhan competitions. The event was attended by 85 participants from kindergarten, elementary, and junior high school levels. The activities were lively and well-received by the community despite challenges such as rainy weather. Overall, the Children's Festival successfully enhanced children's self-confidence, sportsmanship, and provided a platform for them to express their talents and creativity.